A régiók fejlődése és a szubnacionális mobilizáció az Európai Unióban: The Advancement of Regions, and the Subnational Mobilisation in the European Union - Dr. Dömők, Csilla (Közép-Európai Közlemények, 2020)
Nem kérdés, hogy Európa egy radikális átalakuláson megy keresztül. Egyszerre figyelhetjük meg Európában a kistérségi egységek és regionális mozgalmak reneszánszát. Az államok szubnacionális egységeiről való politikai, gazdasági és kulturális gondolkodás, valamint cselekvés túlnyomórészt Európában tört utat magának. A regionális mozgalmak nagyobb autonómiát követeltek hatalmi szférájuk és befolyási területük számára, részint erőszakkal, egészen egyes területek különválásáig. Földrajzi, etikai, nyelvi, vallási, kulturális, történelmi vagy gazdasági dimenziók különböző vonatkozási pontjait választották ki, hogy egy ily módon elhatárolt területet régióként jelöljenek. Azok a közös jellemzők, melyeknek egy régió lakói birtokában vannak, megteremtik a speciális egység érzését és a regionális identitást. Nagy jelentőséggel bír az Európai Unión belüli régiók rendkívül széles palettája a szubnacionális egységek jogi státuszát, kompetenciáit, valamint pénzügyi forrásait és ezáltal politikai minőségét illetően. Subnational mobilisation was one of the most outstanding features of the European internal policy of the 1990s. The phenomenon is reflected by two, mutually reinforcing factors. On the one hand, the 1988 reform of the Structural Funds and several provisions and principles of TEU created new opportunities for regions to become involved in the European politics; on the other hand, processes and theoretical debates towards the territorial decentralisation of power within Member States, as well as the openness and activism of regions in the area of structural and cohesion policy expressed more and more pronounced needs of enforcement of their rights. The opportunities and demands, the “Europe of the regions”, the concept of a “Three-tier Europe” together with the EU becoming a multi-level governance system collectively constitute the conditionality of subnational mobilisation. The phenomenon can be summarised as follows: the regions within the state and at Community level, by the concurrent use of institutional and informal tools, are increasingly becoming involved and are increasingly becoming involved and are increasingly shaping the EU institutions and their decision-making processes.